2007
DOI: 10.1380/ejssnt.2007.103
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Unidirectionally Oriented Pentacene Nanofibers by a Roller Method

Abstract: Oriented crystal fibers of pentacene were produced by a simple casting process from trichlorobenzene solution at elevated temperature. The solution was placed in the air gap between a glass roller and a glass substrate. The width of the air gap was determined by a Teflon spacer wound around both ends of the roller. The roller was moved over the substrate with a constant speed and crystal fibers with approx. 100 nm height, micrometer width and a length of up to 100 µm were formed in the rolling direction. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The charge carrier mobility in crystalline fibers made of pentacene [18] is in the range of 0.1 -1 cm 2 V -1 s -1 [19] which is in the same range as the values reported by others for bottom contact field effect transistors (FETs) [20,21].…”
Section: Electronic and Photonics Applicationssupporting
confidence: 85%
See 1 more Smart Citation
“…The charge carrier mobility in crystalline fibers made of pentacene [18] is in the range of 0.1 -1 cm 2 V -1 s -1 [19] which is in the same range as the values reported by others for bottom contact field effect transistors (FETs) [20,21].…”
Section: Electronic and Photonics Applicationssupporting
confidence: 85%
“…Glass and silicon substrates were cleaned by sonication in alcoholic potassium hydroxide solution, followed by rinsing with water and acetone. The used roller apparatus was described in detail earlier [18,19]. Gold microelectrode patterns were prepared in-house by a lift-off technique.…”
Section: Methodsmentioning
confidence: 99%
“…Oriented pentacene fibers were prepared by a method already reported [5]. A hot solution of pentacene in trichlorobenzene is placed in a heated roller apparatus, and the roller is pulled over the substrate with a constant speed.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a wet process could be used to overcome the problem of grain boundaries, since organic compounds, in principle, can form single crystals when recrystallized from solution. Recently it has been reported that pentacene can be spin cast from hot trichlorobenzene solution [4] and we have described the formation of parallel aligned pentacene microfibers by using a hot trichlorobenzene solution and a roller apparatus [5]. This self-patterning is one example for a mask-less process to produce micropatterns very well suited for the mass production of transistor arrays.…”
Section: Introductionmentioning
confidence: 98%